Living in Ireland survey: Technical report and codebook for data users - Dorothy Watson (The Economic and Social Research Institute (ESRI), 2004)
This document provides a brief technical overview of the Living in Ireland Surveys and of the dataset lodged with the Irish Social Science Data Archive. Section 1 describes the Living in Ireland Surveys. Section 2 focuses on the structure of the data files, and Section 3 is a detailed codebook.
Keywords: 330